Delgadobius amazonensis—a new genus and species of the subtribe Philonthina from Amazonia (Coleoptera: Staphylinidae: Staphylininae) - Chani Posse, Mariana Raquel (2012)
Delgadobius amazonensis Chani-Posse & Couturier, gen. et sp. nov., a new genus and species of the subtribe Philonthina (tribe Staphylinini) from Amazonia, is described and illustrated. The potential phylogenetic relationships of Delgadobius with other Neotropical genera of Philonthina are discussed. Distributional and bionomic data are also provided. Delgadobius amazonensis is reported in association with four species of palm trees (Arecaceae).